The effect of ethanol extract of Aloysia triphylla on anesthesia and improve the physiological parameters of rainbow trout (Oncorhynchus mykiss) after transfer - Ali Hajibeglou; Masoumeh Machanlou; Mohammad Mazandarani; Mohammad Sudagar (تغذیه آبزیان)
Introduction: Due to the side effects of chemical drugs, in recent years, the use of herbal medicines and their compounds in fish has been widely considered. The use of medicinal plants and their derivatives can stimulate feed consumption, increase daily weight, feed conversion ratio, increase shelf life, improve the health and function of the digestive system, minimize or mitigate the effects of stress on fish. Lemon herbena (Aloysia triphylla) is a member of Verbenaceae family. This plant is endemic to South America and can growth in other areas, such as Iran. This study was performed to evaluate the effect of Aloysia triphylla extract on anaesthesia, some water quality parameters, and haematology in juveniles rainbow trout, Oncorhynchus mykiss with average weight of 7 ± 0.42 g after transport. Materials and methods: The experiment was divided in three steps: 1: the anesthesia induction with Aloysia triphylla: 0 (control), 25, 50, 100, 200, and 400 μL/L; 2: transport for 4 h with the fish separated into three groups: control and two concentrations of A. triphylla: 12.5 and 25 μL/L; and, 3: determination of the ventilatory frequency in fish exposed to A. triphylla at 12.5 or 25 μL/L. Results and discussion: The results showed that the elevated concentration of A. triphylla proportionally decreased the time required for sedation and anesthesia induction and upraised the recovery time. After transport, lower blood serum glucose and cortisol and higher total protein, albumin, non-ionized ammonia, and dissolved oxygen levels in water were observed in fish exposed to 12.5 and 25 μL/L of the extract (p<0.05). By increasing the exposure time to A. triphylla, lower ventilatory frequency was found in fish exposed to 25 μL/L of extract (p<0.05). Conclusions: In general, these results indicated that A. triphylla may have sedative and anesthetic effects on rainbow trout. Finally, it can be used to reduce the negative effects of stress caused by fish manipulation and transportation. Conflicts of interest: Authors have no conflict of interest to declare for the publication of the present work Funding: Authors have no sources of funding for the present work. Acknowledgments: The authors would like to express their support offered by the University of Agricultural Sciences and Natural Resources of Gorgan, Iran.